Protection of civilians in armed conflicts: Estonian experience - Ірина Шопіна; Сергій Тарасов (Social Development & Security, 2019)
The article contains an analysis of the laws and regulations of the Republic of Estonia that cover protection of civilians. It is also including the role, functions and tasks of the subjects of protection of the civilians during: crisis informing, evacuation, preemptive actions and emergency assistance to the population during a crisis. In addition, possible ways to increase the awareness of the civilian population of the Republic of Estonia in the event of a crisis are analyzed.